2019
DOI: 10.1002/slct.201903210
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Epoxy/GO Composites Mechanical and Thermal Properties by Removing Air Bubbles with Shear Mixing and Ultrasonication

Abstract: Epoxy‐graphene oxide composites were prepared through the homogeneous dispersion of graphene oxide (GO) in epoxy via shear mixing and ultrasonication techniques. Mechanical and thermal properties of the composites were evaluated. Final composite samples were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, optical microscope, differential scanning calorimetry, thermogravimetric analysis, and x‐ray diffraction analyses. The thickness of the prepared GO sheet was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…[27,30] The use of GO and GO-derived graphene materials as a filler in polymer composites not only have increased the elastic modulus and tensile strength of the composites, but also added electrical conductivity and thermal stability, which creates the potential to produce a multifunctional composite. [29,[31][32][33] By adding 0.7 wt% GO in poly(vinyl alcohol) (PVA) an increase of 62% in Young's modulus and 76% in tensile strength were achieved due to efficient load transfer between the GO and the matrix. [34] Many studies have been reported on the coating of synthetic fibers with GO [35,36] to increase the composite performance, including the mechanical and interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…[27,30] The use of GO and GO-derived graphene materials as a filler in polymer composites not only have increased the elastic modulus and tensile strength of the composites, but also added electrical conductivity and thermal stability, which creates the potential to produce a multifunctional composite. [29,[31][32][33] By adding 0.7 wt% GO in poly(vinyl alcohol) (PVA) an increase of 62% in Young's modulus and 76% in tensile strength were achieved due to efficient load transfer between the GO and the matrix. [34] Many studies have been reported on the coating of synthetic fibers with GO [35,36] to increase the composite performance, including the mechanical and interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the elongation at the break of the tested paint films appears to display the opposite rule with the increasing dosage of GO. Excessive GO would impair the toughness of the composite paint films (Figure 4h), probably due to the promoted crystallinity of PU through enhancing the intermolecular forces and reducing the slip among the resin molecular chains [52]. The composite film of GO-WPU at 0.1 wt% shows benign elongation at break, with a slight decrease (1.7%) compared with the GO-free paint film.…”
Section: Resultsmentioning
confidence: 99%
“…This stability allows GO-based SCs to maintain their performance over extended periods, making them a reliable energy storage solution. 76,77 Also, the mechanical properties of GO have been extensively studied, and it has been found to be structurally very stable and highly fracture-resistant. 78 Furthermore, GO is highly compatible with existing manufacturing techniques, enabling its integration into various electrode architectures.…”
Section: Advantages and Disadvantages Of Go In Sc Technologymentioning
confidence: 99%